Long-term outcomes of mesohepatectomy for centrally located liver tumors: two-decade single-center experience - Mehrabi, Arianeb; Ramouz, Ali; Golriz, Mohammad; Khajeh, Elias; Hackert, Thilo; Müller, Beat P.; Strobel, Oliver; Hoffmann, Katrin; Büchler, Markus W.; Ünal, Umut Kaan; Ghamarnejad, Omid; Mieth, Markus; et al. (Journal of the American College of Surgeons, 2022)
Export - BACKGROUND: Mesohepatectomy is a viable treatment option for patients diagnosed with centrally located liver tumors (CLLTs). There are several reports from Eastern centers, but few data are available on this topic from Western centers. - STUDY DESIGN: - Data of 128 consecutive patients who underwent mesohepatectomy between September 2000 and September 2020 in our center were analyzed from a prospectively collected database. Patient demographic data, liver tumor characteristics, and intraoperative data were collected. In addition, posthepatectomy bile leakage (PHBL), posthepatectomy hemorrhage (PHH), posthepatectomy liver failure (PHLF), and 90-day mortality after mesohepatectomy were assessed. Long-term outcomes were also reported, and factors that may influence disease-free survival were evaluated. - RESULTS: - Of 128 patients, 113 patients (88.3%) had malignant hepatic tumors (primary and metastatic tumors in 41 [32%] and 72 [56.3%] patients, respectively), and 15 patients suffered from benign lesions (11.7%). Among the relevant surgical complications (grade B or C), PHBL was the most common complication after mesohepatectomy and occurred in 11.7% of patients, followed by PHLF in 3.1% of patients and PHH in 2.3% of patients. Only four patients (3.1%) died within 90 days after mesohepatectomy. The 5-year overall survival and overall recurrence (for malignant lesion) rates were 76.5% and 45.1%, respectively. - CONCLUSION: - Mesohepatectomy is a safe and feasible surgical treatment with low morbidity and mortality for patients with CLLT. Long-term outcomes can be improved by increased surgical expertise.